(untitled) (Circe de clásicos y modernos, 2021)
It is offered here a Spanish translation of the Ἀμαθής, with introduction, notes and interpreting commentary; it is highlighted that this work represents the genre satura in Byzantium, according to a large tradition assumed by the ‘classicism’ of the XIIth century.